The Mediating Role of Multidimensional Customer Brand Engagement on Brand Loyalty - Faradila, Ade Putri; Siagian, Yolanda Masnita (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the influence of social media marketing efforts on brand loyalty, mediated by the multidimensional customer brand engagement in airlines in Indonesia. The object of this research is national airlines, with the population comprising respondents who follow or have interacted (such as liking, commenting, and sharing) with the social media accounts of national airlines at least once in the last 30 days. The sample used consists of 220 respondents. The analysis employed is SEM with the help of SPSS and AMOS version 23 software. The results of this study indicate that social media marketing efforts have a positive influence on cognitive engagement, social media marketing efforts have a positive influence on emotional engagement, social media marketing efforts do not have a positive influence on brand loyalty, cognitive engagement has a positive influence on brand loyalty, emotional engagement has a positive influence on brand loyalty, social media marketing efforts have a positive influence on brand loyalty mediated by cognitive engagement, and social media marketing efforts have a positive influence on brand loyalty mediated by emotional engagement.